1995
DOI: 10.1007/bf00194331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ACE inhibition on endurance exercise haemodynamics in trained subjects with mild hypertension

Abstract: The aim of the study was to examine the effect of chronic angiotensin converting enzyme inhibition on haemodynamics and left ventricular performance during long-lasting exercise at the anaerobic threshold. For this purpose exercise haemodynamics and left ventricular performance were assessed in 14 physically trained hypertensives (aged 26 y) before and after 3 months on quinapril 20 mg once daily. During exercise intraarterial blood pressure was monitored using the Oxford method and left ventricular dimensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Systemic angiotensin II levels and blood pressure seem to be unaffected by the ACE ID genotyperelated variation in plasma ACE levels (17). In addition, treatment with ACE inhibitors causes a drastic decrease in ACE activity and angiotensin II levels but has no effect on endurance performance in healthy or mildly hypertensive subjects (2,27,28). It has been suggested that the greater ACE II genotype frequency in endurance athletes could reflect the selection of individuals with a ''healthier'' cardiovascular system and, thus a higher aerobic capacity (12,24,26).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic angiotensin II levels and blood pressure seem to be unaffected by the ACE ID genotyperelated variation in plasma ACE levels (17). In addition, treatment with ACE inhibitors causes a drastic decrease in ACE activity and angiotensin II levels but has no effect on endurance performance in healthy or mildly hypertensive subjects (2,27,28). It has been suggested that the greater ACE II genotype frequency in endurance athletes could reflect the selection of individuals with a ''healthier'' cardiovascular system and, thus a higher aerobic capacity (12,24,26).…”
Section: Discussionmentioning
confidence: 99%
“…Although the renin-angiotensin system does interact with the sympathetic nervous system, this control is primarily involved in the regulation of peripheral vascular smooth muscle tone (9) and not central CV chronotropic responses. In fact, angiotensin I infusions have, at best, only a minimal impact on HR (7,21). Furthermore, angiotensin converting enzyme (ACE) inhibitors are believed to be an optimal medication for hypertensives who want to exercise, because they have negligible effects on exercise HR responses and maximal exercise capacities (12,21).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, angiotensin I infusions have, at best, only a minimal impact on HR (7,21). Furthermore, angiotensin converting enzyme (ACE) inhibitors are believed to be an optimal medication for hypertensives who want to exercise, because they have negligible effects on exercise HR responses and maximal exercise capacities (12,21). Thus it is entirely possible that the AGT M235T locus is simply a marker for another adjacent genetic variant that may be within the sympathetic nervous system and which would be better linked, in mechanistic terms, to our findings of altered exercise HR responses associated with AGT M235T genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus ACE inhibition did not alter oxidative capacity, in line with the maintained endurance capacity of the animals. Similarly, in trained human subjects with or without mild hypertension, ACE inhibition does not affect endurance exercise hemodynamics and V O 2 max or parameters of energy metabolism (26,28).…”
Section: Discussionmentioning
confidence: 99%